2018
DOI: 10.1093/nar/gky728
|View full text |Cite
|
Sign up to set email alerts
|

A piRNA utilizes HILI and HIWI2 mediated pathway to down-regulate ferritin heavy chain 1 mRNA in human somatic cells

Abstract: The piwi interacting RNAs (piRNAs) are small non-coding RNAs that specifically bind to the PIWI proteins, a functional requirement. The piRNAs regulate germline development, transposons control, and gene expression. However, piRNA-mediated post-transcriptional gene regulation in human somatic cells is not well understood. We discovered a human piRNA (piR-FTH1) which has a complementary sequence in the ferritin heavy chain 1 (Fth1) mRNA. We demonstrated that expression of piR-FTH1 and Fth1 are inversely correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 78 publications
(100 reference statements)
0
24
0
Order By: Relevance
“…piRNAs have predominantly been linked to germ cell/stem cell development and maintenance and transposon regulation [12,13,14,15]. However, several studies have also demonstrated their gene regulatory potential in somatic cells [16,17]. Furthermore, the stability of piRNAs in body fluids has also opened up the possibility that piRNAs might serve as circulating biomarkers [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…piRNAs have predominantly been linked to germ cell/stem cell development and maintenance and transposon regulation [12,13,14,15]. However, several studies have also demonstrated their gene regulatory potential in somatic cells [16,17]. Furthermore, the stability of piRNAs in body fluids has also opened up the possibility that piRNAs might serve as circulating biomarkers [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, chemical modifications of antagomiRs determine microRNA fate by targeting it for degradation or accumulation in heteroduplexes [115, 138141]. Interestingly, possibilities of piRNA chemical modifications are much less well explored, despite the fact that naturally existing piRNAs incorporate the 3′-end 2′- O -methyl modification that protects them from RNases [184].…”
Section: Introductionmentioning
confidence: 99%
“…Second, piRNAs also regulate gene expression at the post-transcriptional level via alternative splicing or controlling mRNA stability, and RNA endonucleolytic cleavage or interaction with RNAs 54,55. In general, piRNAs target the transposon sequences found in the 3′-UTRs or 5′-UTRs of mRNAs, and piRNAs derived from pseudogenes and antisense transcripts also target the mRNA of the corresponding endogenous gene, resulting in mRNA deadenylation or degradation 15,5658. Several studies have confirmed the relationship between piRNAs and their target mRNAs 56,59–61.…”
Section: Mechanisms Of Action Of Pirnasmentioning
confidence: 99%